Effects of interactive digital media on architectural heritage learning - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen; Mahmud, Murni (Universiti Teknologi Malaysia, 2016)
This study attempts to determine the effects of three modes of digital media (virtual reality, video, and Web) on architectural heritage learning. It also aims to determine the demographics' effects of museum visitors on learning using interactive digital media. The content of these media focuses on historical and architectural information of a cultural heritage monument at a UNESCO World Heritage Site. This study has employed quasi-experimental method with the use of designated tasks and retention test in real-world setting. It is found that there is a significant difference among these digital media on retention score. Further analysis reveals that virtual reality provides the lowest retention score and contributes to this significant difference when compared to video. There is no significant difference between gender and retention score. However, there is a significant difference among age and retention score. This study contributes towards empirical evidence on the significant use of interactive digital media on architectural heritage learning and provides insights about demographic effects of interactive digital media on architectural heritage learning.